(untitled) (Novateur Publications, 2025)
The modern financial world is undergoing a significant transformation driven by the convergence of banking and digital technology. The integration of digital technologies is no longer just a strategic option for banks; it’s essential for their survival and growth in today’s digitally focused environment. From online banking platforms to the adoption of advanced technologies like artificial intelligence and blockchain, digitization has fundamentally reshaped how customers interact with financial institutions.